2005
DOI: 10.1007/s00775-005-0661-5
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of Mo-/Cu-dependent CO dehydrogenase

Abstract: Density functional theory computations at the B3LYP/SDDp//B3LYP/Lanl2DZ level were performed on model complexes derived from [(Me(2)C(2)S(2))Mo(O)(2)-S-CuSMe](2-) or its oxo protonated form to gain insight into the reaction steps involved in substrate oxidation of a Mo-/Cu-dependent CO dehydrogenase. Only the bisoxo but not the hydroxo oxo complex was found to oxidize CO exothermically. A thiocarbamate complex structurally characterized as the reaction product of the enzyme with the inhibitor n-butylisonitrile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 20 publications
6
89
0
Order By: Relevance
“…reduction of protons to H 2 ), as seen with the Ni-Fe CO dehydrogenases, suggests that deprotonation of the copper hydride intermediate is strongly downhill thermodynamically and functionally irreversible (15). Nevertheless, there are common elements of the reaction mechanism proposed here for reduction by H 2 and that proposed previously for reduction by CO (11,12). These include initial binding of substrate to the copper of the binuclear center in a manner that activates substrate (by back-bonding from copper into a * orbit in the case of CO, by polarization of the H-H bond in the case of H 2 ) and utilization of the highly delocalized nature of the redox-active orbital of the binuclear center to bring about its reduction via the copper rather than the molybdenum.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…reduction of protons to H 2 ), as seen with the Ni-Fe CO dehydrogenases, suggests that deprotonation of the copper hydride intermediate is strongly downhill thermodynamically and functionally irreversible (15). Nevertheless, there are common elements of the reaction mechanism proposed here for reduction by H 2 and that proposed previously for reduction by CO (11,12). These include initial binding of substrate to the copper of the binuclear center in a manner that activates substrate (by back-bonding from copper into a * orbit in the case of CO, by polarization of the H-H bond in the case of H 2 ) and utilization of the highly delocalized nature of the redox-active orbital of the binuclear center to bring about its reduction via the copper rather than the molybdenum.…”
Section: Discussionmentioning
confidence: 58%
“…We consider it unlikely that bicarbonate displaces only the equatorial MoϭO of oxidized enzyme (to give a Mo(V)/Cu(I) species analogous to a presumed Mo(VI)/Cu(I) intermediate proposed on the basis of computational studies (11,12), as this does not account for the experimentally observed loss of proton coupling in the EPR signal in the presence of bicarbonate. Finally, with the H 2 -reduced native enzyme, given the effectiveness with which CO dehydrogenase oxidizes H 2 , we consider it very likely that that, as has been proposed for CO oxidation where CO initially binds to the copper of the binuclear center, H 2 also first binds at the copper of the binuclear center (11,12), displacing the H 2 O coordinated to the copper prior to catalysis. We believe that the observed EPR signal (as with CO as substrate) arises from enzyme that has already become partially reduced by reaction with prior turnover under the reaction conditions, such that H 2 is bound to a partially reduced Mo(V)/Cu(I) binuclear center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been two previous studies on the mechanism of Mo,Cu-dependent CO dehydrogenase. [25,44] An important finding in these studies was the presence of intermediates with SÀC bonds, one of them shown to the right in Figure 5. The structure to the left is the one without substrate, which has a MoÀCu bond length of 2.97 .…”
Section: Mocu-dependent Co Dehydrogenasementioning
confidence: 98%
“…A reaction mechanism has been proposed involving the formation of an SCO 2 intermediate, on the basis of the crystal structure of CODH in complex with the inhibitor n-butylisocyanide (7). However, computational studies suggest that such a thiocarbonate intermediate actually leads to a deep minimum on the potential energy surface, making CO 2 release extremely difficult (16,17). In addition, model compound studies suggest that CO oxidation could occur directly at the Cu(I) site, followed by electron transfer to Mo via the electronic delocalization of the Mo(-S)Cu moiety (18).…”
mentioning
confidence: 99%